Upaya Meningkatkan Kemandirian Anak Kelompok A Dengan Modifikasi Perilaku Pendekatan Positif DI TK Kemiri 05 Kebakkramat Karangnyar Tahun Ajaran 2015/2016 - sari, defi nur mela; , Drs. Ilham Sunaryo, M.Pd AUD (2016)
This study aims to increase the independence of children in toilet training for group A in TK Kemiri 05 Kebakkramat positive behavior modification approach.This research is a classroom action research conducted in two cycles each cycle consisting of two meet. This research was conducted kalaboratif between researcher and teacher. Subjects in the study were 20 children in group A kindergarten Kemiri 05 Kebakkramat consisting of 9 boys and 11 girls. Object under investigation is an activity the child's independence. Data collection techniques in this study using observation and field notes. The data were analyzed by using comparative analysis and interactive.The results showed that the child's independence has increased in each cycle. Such improvements can be seen in the initial condition of the child's independence by 49.0% in group A, the first cycle of 63.8%, and the second cycle of 82.0%. The conclusion of this study, with a positive approach to behavior modification can increase self-reliance in toilet training for children in group A of TK 05 Kebakkramat Academic Year 2015/2016. Keywords: independence, behavior modification positive approach.